Beliefs about back pain predict the recovery rate over 52 consecutive weeks - Elfering, Achim; Mannion, Anne F.; Jacobshagen, Nicola; Tamcan, Oezguer; Müller, Urs (Scandinavian Journal of Work, Environment & Health, 2009)
' ' OBJECTIVES ': 'This study examined the course of low-back pain over 52 weeks following current pain at baseline. Initial beliefs about the inevitability of the pain’s negative consequences and fear avoidance beliefs were examined as potential risk factors for persistent low-back pain. ' ' METHODS ': 'On a weekly basis over a period of one year, 264 participants reported both the intensity and frequency of their low-back pain and the degree to which it impaired their work performance. In a multilevel regression analysis, predictor variables included initial low-back pain intensity, age, gender, body mass index, anxiety/depression, participation in sport, heavy workload, time (1–52 weeks), and scores on the “back beliefs” and “fear-avoidance beliefs” questionnaires. ' ' RESULTS ': 'The group mean values for both the intensity and frequency of weekly low-back pain, and the impairment of work performance due to such pain showed a recovery within the first 12 weeks. In a multilevel regression of 9497 weekly measurements, greater weekly low-back pain and impairment were predicted by higher levels of work-related fear avoidance beliefs. A significant interaction between time and the scores on both the work-related fear-avoidance and back beliefs questionnaires indicated faster recovery and pain relief over time in those who reported less fear-avoidance and fewer negative beliefs. ' ' CONCLUSIONS ': 'Negative beliefs about the inevitability of adverse consequences of low-back pain and work-related, fear-avoidance beliefs are independent risk factors for poor recovery from low-back pain.
Keywords: back pain; back pain belief; belief; low-back pain; multilevel model; prediction; recovery rate; work performance